CRIMINAL LIABILITY FOR THE TRAFFICKING IN COUNTERFEITED MEDICINAL PRODUCTS:: PROBLEMS OF LEGISLATION AND ENFORCEMENT IN UKRAINE - Y. Konopelskyi, Viktor; O. Merkulova, Valentyna; A. Hrytenko, Oksana; M. Kulyk, Liudmyla (Gênero & Direito, 2020)
The paper focuses on consideration of factors of international, socio-economic and legal nature that determine the dynamics and content of criminal liability for trafficking in counterfeit medicines in Ukraine. Some discussion points, both theoretical and legal, concerning trafficking in counterfeit medicines are considered. Attention is drawn to the fact that counterfeits’ volume is highly dependent on the amount of patent advertising of medicines, which is an appropriate benchmark for criminals who manufacture low-quality and unregistered medicines, mainly in underground handicraft production. Particular attention is paid to the ratio of counterfeiting and patent advertising of medicines. It is investigated Art. 321-1 of the Criminal Code of Ukraine, in accordance with the perfection and clarity of legislative definitions, their compliance with requirements of systematic interrelation of criminal law provisions, justice principles and differentiation of criminal liability. It is proved that it is important to develop our own legislative and enforcement experience in the field of preventing the trafficking in of counterfeit medicines, systematic principled approaches in the part of regulatory legal formulations and their judicial interpretation during practical application. In particular, the improvement of the criminal law in terms of ensuring the clarity of penal provisions contained in Art. 321-1 of the Criminal Code of Ukraine, as well as determining the place and role of the relevant article of the Criminal Code in the system of other criminal legal norms that affect the population health.